A Histological and Clinical Evaluation of Plasma as a Graft Holding Solution and Its Efficacy in Terms of Hair Growth and Graft Survival - Anil Kumar Garg; Seema Garg (Indian Journal of Plastic Surgery)
Background There is a time lag between hair follicle harvesting and implantation, during this time hair follicles suffer ischemic injury. We need a holding medium or a solution to minimize or neutralize ischemic injury. Aims and Objective To evaluate plasma as a graft holding solution in terms of its efficacy in hair growth and hair graft survival. Method and Material A split scalp study was performed. The left side was designated as the control area (Group A) where grafts implanted were kept in Ringer’s lactate, and the right side behaved as the test area (Group B) and received grafts preserved in autologous plasma. The p-value was calculated. Observations MTT staining for grafts stored in Ringer’s lactate at 12 and 72 hours showed poor hair follicle cells’ survival while grafts kept in plasma showed viable cells even after 72 hours. The hair count and density in plasma group were significantly higher than those in the Ringer’s lactate group. There was an improvement in hair thickness in both groups from 6 months to 12 months. Conclusion Autologous plasma is an easily available graft holding solution. Platelets along with the plasma provide multiple growth factors promoting epithelialization, neovascularization, and action on hair follicle stem cells to improve growth. The fibrin coating around the graft makes it sticky and prevents dehydration. The split scalp controlled study certainly shows the advantages of using plasma over other extra cellular graft holding solutions.